Use of Behavior Modification with L. D. Students Frank P. Belcastro. - Belcastro, Frank P. (Distributed by ERIC Clearinghouse, 1977)
Reviewed was research on the application of operant conditioning techniques to the modification of the classroom behavior of learning disabled students. The methodology and results of the studies were examined and each study summarized. It was concluded that there was little common interpretation of the term "learning disabilities" and that all of the studies had violated one or more of the following requirements of good experimental design: (1) adequate description of subjects, (2) proper sampling techniques, (3) adequate control procedures, (4) statistical analysis of the data, and (5) evaluation of long-term gains. (Author/IM)